Kinerja Simpang Bersinyal Jalan Abdullah Daeng Sirua – Batua Raya – Taman Makam Pahlawan Kota Makassar - Febry Gita Kendek; Rais Rachman; Louise Elizabeth Radjawane (Paulus Civil Engineering Journal, 2020)
This study aims to analyze the performance of signalized intersections in urban commercial areas using the MKJI 1997 method. The research location is Abdullah Daeng Sirua junction - Batua Raya Street - Jalan Taman Makam Pahlawan. The vehicles observed were classified by type, namely motorcycle, light vehicles and heavy vehicles. Based on the results of the study obtained the highest degree of saturation degree 1.4 occurred during the evening rush hour and the lowest during the afternoon rush hour of 0.8. The relationship of current to capacity, the relationship of current to the queue, and the relationship of the current to the delay at the intersection of the Abdullah Daeng Sirua road - Taman Makam Pahlawan Street - Jalan Batua Raya is directly proportional where the greater the current value, the greater the capacity, queue and delay.